Preparation, usage, returning and expiration of blood: 4- year overview from registry data of King Chulalongkorn Memorial Hospital - Wiwanitkit, Viroj (Srinagarind Medical Journal, 2013)
In the present day, blood becomes an important in vivo product for therapy of many patients. Seeking for blood donor has been continuous promoted. However, pattern of blood using by the physician is still another interesting item to be considered. An analysis on registry data about preparation, usage, returning and expiration of blood of King Chulalongkorn Memorial Hospital during the 4-year period, 1996 - 1999 was performed. Average amount of preparation for all division in the hospital was 53,529 unit/year. Average amount of usage for all division in the hospital was 33,268.5 unit/year. Average amount of returning for all division in the hospital was 22,170.5 unit/year. Average amount of expiration for all division in the hospital was 985.25 unit/year (by both expiration before expired date and expiration by expired date). Further analysis on blood transfusion reaction was also performed and gave average amount equal to 48 case/year (allergy 28 case/year, febrile 20 case/year).